2015
DOI: 10.1609/aaai.v29i1.9335
|View full text |Cite
|
Sign up to set email alerts
|

When Suboptimal Rules

Abstract: This paper represents a paradigm shift in what advice agents should provide people. Contrary to what was previously thought, we empirically show that agents that dispense optimal advice will not necessary facilitate the best improvement in people's strategies. Instead, we claim that agents should at times suboptimally advise. We provide results demonstrating the effectiveness of a suboptimal advising approach in extensive experiments in two canonical mixed agent-human advice-giving domains. Our proposed gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Designers may have bounds and biases, and may not possess complete knowledge. These factors can lead them to behave in ways that appear irrational to the assistant (Elmalech et al 2015). To mitigate the effect of this, the assistant must adapt its choice of interactions to these factors (De Peuter and Kaski 2023).…”
Section: Creating a Collaborative Assistantmentioning
confidence: 99%
See 1 more Smart Citation
“…Designers may have bounds and biases, and may not possess complete knowledge. These factors can lead them to behave in ways that appear irrational to the assistant (Elmalech et al 2015). To mitigate the effect of this, the assistant must adapt its choice of interactions to these factors (De Peuter and Kaski 2023).…”
Section: Creating a Collaborative Assistantmentioning
confidence: 99%
“…We will call these behavioral factors. It is important that these are accounted for and inferred jointly with the designer's goals (De Peuter and Kaski 2023;Elmalech et al 2015). For example, an anchoring bias can cause a designer to fixate on their current design and refuse large changes proposed by an assistant.…”
Section: Introductionmentioning
confidence: 99%
“…Sarne et al (2011) have shown that users' performance can be substantially improved through manipulating the input (for example, the information concerning the different choices) that they receive. Elmalech et al (2015) suggest an approach according to which the decision regarding the advice to be provided should not be made merely based on the encapsulated utility, but rather also based on the likelihood of its acceptance by the user. Das, Mathieu, and Ricketts (2009) theoretically analyze a recommender system that tries to maximize its own expect-ed utility.…”
Section: Related Workmentioning
confidence: 99%
“…Elmalech et al (2015) suggest an approach according to which the decision regarding the advice to be provided should not be made merely based on the encapsulated utility, but rather also based on the likelihood of its acceptance by the user. Das, Mathieu, and Ricketts (2009) theoretically analyze a recommender system that tries to maximize its own expected utility.…”
Section: Related Workmentioning
confidence: 99%
“…Recent progress that has been made in the development of automated agents which can interact proficiently with people, including negotiation agents (Rosenfeld et al 2014b;Dsouza et al 2013;Vahidov, Kersten, and Saade 2012;de Melo, Carnevale, and Gratch 2011;Gal et al 2012;Oshrat, Lin, and Kraus 2009;Lin et al 2008), advice and service provision agents (Azaria et al 2012;Delecroix, Morge, and Routier 2013;Elmalech et al 2015), automated mediators (Lin, Gev, and Kraus 2011), discussion agents (Fenster, Zuckerman, and Kraus 2012;Ren et al 2014) and persuasion agents (Azaria, Aumann, and Kraus 2014), can be the basis for the development of agents capable of performing all four tasks. We will discuss a few ideas and difficulties in relation to such agents in this extended abstract.…”
Section: Encouragementmentioning
confidence: 99%